A simulated gastrointestinal tract study of texturized rice grains: Impact of texturization on starch digestibility. (September 2019) - Ye, Jiangping; Liu, Chengmei; Luo, Shunjing; Wu, Jianyong; Hu, Xiuting; McClements, David Julian
Abstract: The digestibility of starch in cooked ordinary rice grains and cooked texturized rice grains was compared using an in vitro gastrointestinal tract (GIT), which involved sequentially exposing samples to simulated oral, gastric, and small intestinal regions. The total extent of starch hydrolysis (%) of texturized rice was slightly lower than that of ordinary rice by the end of the GIT, probably because of its higher resistant starch content. Furthermore, the rate of starch hydrolysis in the small intestine was much slower for texturized rice than ordinary rice. Gel electrophoresis and microstructure analysis suggested that the proteins in the texturized rice formed a cross-linked network around the starch molecules. This network may have retarded the ability of digestive enzymes to access the starch, thereby reducing the hydrolysis rate. These results have important implications for the design of starch-based foods with a lower glycemic index, and therefore improved nutritional profiles. Graphical abstract: Image 1 Highlights: The simulated gastrointestinal tract was first used to evaluate the digestibility of texturized rice grains. Texturized rice grains had a slower starch digestibility in simulated gastrointestinal tract digestion. Proteins formed cross-linked structure in texturized rice. Texturized rice had a compact structure.